2012
DOI: 10.1002/ccd.23464
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease and the risk of stent thrombosis after percutaneous coronary intervention with drug‐eluting stents

Abstract: CKD is significantly associated with increased incidence of 1-year definite or probable ST in patients undergoing PCI with DES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 52 publications
2
18
0
Order By: Relevance
“…As reported elsewhere, the CKD-EPI equation staged fewer patients to CKD than MDRD formula [21] and in our population produced a predicting ability for stent thrombosis events, posing a possible value for implementation in risk stratification algorithms. Our findings are in accordance to other studies [22] expressing the hypothesis that renal impairment is a significant risk factor for ST.…”
Section: Discussionsupporting
confidence: 96%
“…As reported elsewhere, the CKD-EPI equation staged fewer patients to CKD than MDRD formula [21] and in our population produced a predicting ability for stent thrombosis events, posing a possible value for implementation in risk stratification algorithms. Our findings are in accordance to other studies [22] expressing the hypothesis that renal impairment is a significant risk factor for ST.…”
Section: Discussionsupporting
confidence: 96%
“…Patients with CKD more often had a multivessel disease and PCI of saphenous vein graft as compared to patients with a normal eGFR, which is in keeping with previous observations [11,14,16,23]. In addition to that, CKD patients more often had ST at culprit lesion in our group, which confirmed results of Miao et al [24]. Data from other studies showed that PCI with DES-II in a real-world population is associated with lower risk of clinically meaningful restenosis, ST, and a lower risk of death compared with DES-I [25,26].…”
Section: Discussionsupporting
confidence: 82%
“…The higher prevalence of high platelet reactivity in the CKD population might be another potential explanation for the higher incidence of nonfatal target vessel MI in the CR group than in the IR group among CKD patients. This finding suggests that excessive PCI with DES implantation might be associated with procedure‐related or stent‐related long‐term adverse outcomes rather than the benefit of revascularization as previous studies have suggested 1, 33, 34…”
Section: Discussionmentioning
confidence: 67%